Adoption across Race and Nation US Histories and Legacies - Hackenesch, Silke (The Ohio State University Press, 2022)
Analyzes transnational and transracial adoption, highlighting the past and continuing discourses around adoption as it relates to race, nation, immigration, belonging, and citizenship.